DOKTRIN TASAWUF DALAM KITAB FUSHUS AL-HIKAM KARYA IBN ‘ARABI - Ali Usman (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2019)
Ibn ‘Arabi was an Islamic thinker and a well-known Sufi figure among Sufi figures who had an extraordinary influence on the development of Islamic thought until now. His knowledge and thoughts really have a very high imaginative power, as seen in many of his works, which until now have never been bored by their readers. Fushus al-Hikam, which is his monumental work, besides al-Futuhat al-Makkiyah. The Book of Fushus al-Hikam (Ring of Wisdom Binding / String of Pearls of Wisdom) is a relatively shorter work than the Futuhat, but it is the most widely read and suggested by the reviewer (perhaps because it is the most difficult), as well as the most influential and most famous. This book was compiled in 627 AH / 1229 CE, ten years before he died. According to Ibn ‘Arabi himself, the content in this work was entirely based on the inspiration of his spiritual knowledge from the Prophet who held a book in his hand and he ordered to take it and bring it to the world so that people could benefit from it.